Effect of polyethylene glycol on mechanical properties of bamboo fiber‐reinforced polylactic acid composites. Issue 26 (12th March 2019) - Long, Haibo; Wu, Zhiqiang; Dong, Qianqian; Shen, Yuting; Zhou, Wuyi; Luo, Ying; Zhang, Chaoqun; Dong, Xianming
ABSTRACT: The bamboo fiber (BF)‐reinforced polylactic acid (PLA) composites were prepared using the twin‐screw extruder and injection molding. Thermal gravimetric analyzer results indicated the thermal stability of BF/PLA composites decreased with increasing BF content. Differential scanning calorimeter and X‐ray diffraction curves showed that BF played a role as a nucleating agent, but the crystallinity of composite materials decreased with the increasing BF content. The melt flow rate of composites reduced with the increase in BF content, resulting in a poorer processing property. The processability of the composites was improved with the addition of high molecular polyethylene glycol (PEG). Mechanics performance test showed that tensile strength and bending strength of composites increased at low loading with the BF content increased then decreased when the loading continued to increase. The tensile strength of the composite materials reached 65.46 MPa when alkali‐treated BF (ABF) content was 20 wt %. The flexural strength of the composites reached 97.94 MPa when ABF content was 10 wt %. Impact performance has also been improved. PEG‐20000 was the best plasticizer among the PEG‐6000，PEG‐10000, and PEG‐20000. When the component of PEG was 10 wt %, the elongation increased by 56%. The scanning electron microscopy (SEM) result showed that the fracture of the composites was smooth, most ABF were wrapped in matrix and distribution of ABF in PLA matrix was more uniform. It means that interfacial compatibility of bamboo fiber and PLA improved after BF modified by alkali. High molecular weight PEG enhance melt flow ability of polymer, result in fibers were further enclosed in the PLA matrix and increase properties of composites. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47709. Abstract :